Politiques et pratiques de la psychiatrie en prison 1945-1986 - Hélène Bellanger (Criminocorpus)
Since the penal code of 1810 (section 64) and the 1838 bill on insane persons, psychiatry and prison followed two parallel historical paths : the psychiatrist, being an expert, came in prison only to identify insane and to take him out of jail. Non-insane, half-insane, mentally disabled but also all those disturbing prison order were treated solely according to penitentiary discipline. After the historical break of Second World War, a spirally reform process gradually sealed the historical convergency of prison and asylum, and led to the creation of structures dedicated to psychiatric treatment of prisonners (psychiatric annexes created by Amor reform, followed by the CMPR and SMPR). The institutionalization of psychiatric intervention in prison spred out in more than forty years. In a background of shortages, through failures and experimenting, following various patterns, several generations of practioners, judges and penitentiary officers designed through practice a new frame for sanitary intervention in prison that became a place for medical care.